2016
DOI: 10.1016/j.apergo.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Assessing attentional prioritization of front-of-pack nutrition labels using change detection

Abstract: We used a change detection method to evaluate attentional prioritization of nutrition information that appears in the traditional “Nutrition Facts Panel” and in front-of-pack nutrition labels. Results provide compelling evidence that front-of-pack labels attract attention more readily than the Nutrition Facts Panel, even when participants are not specifically tasked with searching for nutrition information. Further, color-coding the relative nutritional value of key nutrients within the front-of-pack label res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
0
12
0
3
Order By: Relevance
“…Interpretive FoPLs associated with the highest increase in objective understanding were the Nutri-Score and the MTL, which were the only two colour-coded labels among the five FoPLs tested. It has been demonstrated that the use of colours is key regarding FoPL salience, as colours tend to capture attention [ 27 , 31 , 43 , 46 , 47 , 48 , 49 , 50 ]. Moreover, the use of the well-known polychromatic green-red scale might be an important feature of FoPL colour coding.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretive FoPLs associated with the highest increase in objective understanding were the Nutri-Score and the MTL, which were the only two colour-coded labels among the five FoPLs tested. It has been demonstrated that the use of colours is key regarding FoPL salience, as colours tend to capture attention [ 27 , 31 , 43 , 46 , 47 , 48 , 49 , 50 ]. Moreover, the use of the well-known polychromatic green-red scale might be an important feature of FoPL colour coding.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, consumers tend to agree on the fact that the back-ofpack nutritional declaration is difficult to understand [78,79], and the demand for simplified front-of-pack labels [13] is increasing as evidenced by the current upward trend in implementation of FoPLs around the world [80]. Results from studies presenting various FoPL models to consumers suggest that color-coded labels would be preferred by consumers [50,72,81], and summary systems more specifically by more disadvantaged groups [82].…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified several characteristics that increase the effectiveness of FOP systems, including the use of recognizable symbols that are easy to understand [ 28 ]. The use of color has also been shown to increase attention to FOP labels [ 29 , 30 ] and may help consumers to make healthier choices [ 31 , 32 , 33 , 34 ]. Simple directional text, such as ‘high in (nutrient)’ is supported by consumers and has been shown to increase understanding of the healthfulness of products [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%